Uncivil servant - Sethi, Ravi Mohan (New Delhi, 2010)
An Uncivil Servant recounts, vividly the life of a refugee's son, from the lanes of Allahabad to the corridors of bureaucracy. It delves through both the private and the public realms of Ravi Mohan Sethi IAS, and to provide an insider's account of the various trappings of the government.
Keywords: Autobiography-Civil servant